Sistem Informasi Manajemen Keuangan Pada Usaha Dagang Pudor Untuk Meningkatkan Efektifitas Pengelolaan - Jefree fahana; Muhammad Fauzal Hidayat (Universitas Bandar Lampung (UBL), 2025)
This study uses the Waterfall method to develop a web-based Financial Management Information System for Pudor Trading Business. Pudor Trading Business is a company engaged in goods credit services. However, it still uses a manual system for financial management, leading to frequent errors in installment calculations and difficulties in generating financial reports. With the implementation of this system, it is expected to simplify the process of recording transactions, financial reporting, and customer management. The benefits of this research include improving efficiency and accuracy in financial management and facilitating decision-making based on integrated data. The research method used is the Waterfall method, which consists of stages such as requirement analysis, system design, implementation, and testing. Data collection was conducted through observation and interviews with the business owner. The system was developed using PHP programming language and MySQL database, with the CodeIgniter framework to facilitate development. System testing was carried out using Black Box Testing and User Acceptance Testing (UAT) to ensure the system functions according to user needs. The test results show that this financial management information system meets user requirements. Based on UAT results, the majority of respondents provided positive feedback on visual appearance (85.2%), ease of navigation (90.6%), feature usefulness (92%), and website responsiveness (82.6%). The system is considered user-friendly and helpful in managing the financial operations of Pudor Trading Business. Therefore, this system is ready for widespread use and can serve as a solution to enhance the efficiency of financial management in the business.